The Implementation of the Integrated ANC in the Accuracy of Early Detection of Tuberculosis in Pregnancy - Ismi Nur Khasanah (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Tuberculosis has been recognized as a cause of morbidity and mortality during pregnancy, efforts have been made to implement a comprehensive TB screening and treatment program at high risk. The implementation of Integrated ANC is currently not in accordance with standard operating procedures (SOPs) for detecting TB disease in pregnancy. Research Objectives to analyze the implementation of the Integrated ANC in the Accuracy of Early Detection of Tuberculosis in Pregnancy. Sources of data obtained from PubMed and Science Direct. Inclusion Criteria: 1) Midwife, Dentist, General Physician, Laboratory Officer 2) Rapid Assessment Procedure 3) Full text, Articles for 2008-2018, International Journal. The search system uses comprehensive literature search, appraisal studies using the Critical Appraisal Skills Program (CASP), and synthesis methods using PEOS modification. The implementation of TB diagnostic is very limited and there may be an underdiagnosis of TB disease in pregnancy, although screening practices have been carried out, integration of training and supervision of TB diagnosis and treatment into ANC services is still needed. The search for journals from data sources to be analyzed is very limited. Based on the results of the implementation of early detection of TB disease has not been done properly. Undiagnosed still found in several studies. Then it is necessary to further study the accuracy of the diagnosis of tuberculosis.